A novel common‐ground switched‐capacitor five‐level inverter with adaptive hysteresis current control for grid‐connected applications. Issue 12 (20th April 2021) - Barzegarkhoo, Reza; Mojallali, Hamed; Shahalami, Seyed Hamid; Siwakoti, Yam P.
Abstract: The aim of this paper is to present a new topology of single‐phase transformerless inverters, which can be tied to the local grid as a low‐scaled ac module system. The proposed topology offers a common ground between the neutral point of the ac grid and the negative terminal of the dc supply, and can properly alleviate the concern of variable common mode voltage and leakage current problems. This promising feature is acquired by the aim of both the switched‐capacitor and charge pumped circuit cells. In order to inject a tightly controlled ac current to the grid, an adaptive hysteresis current controller scheme is also presented, which can guarantee almost fixed switching frequency operation of the involved power switches. A complete theoretical analysis, comparative study, and the relevant experimental results are also given to confirm the superior performance of the proposed topology.